2021
DOI: 10.3390/agronomy11101905
|View full text |Cite
|
Sign up to set email alerts
|

The Addition of Selenium to the Nutrient Solution Decreases Cadmium Toxicity in Pepper Plants Grown under Hydroponic Conditions

Abstract: Cadmium is absorbed by plants rapidly and without control through the same channels as other essential metals, interfering with their transport and utilization. Many studies have shown that selenium could be utilized as a way to avoid this unwanted transport and other negative effects of Cd. For this reason, the present research study was conducted with four treatments (−Cd/−Se, +Cd/−Se, +Cd/+SeF, and +Cd/+SeR) to determine the type of application of Se that is best (foliarly and/or via the root) as regards th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…In the first part of the present publication [8], it was shown that the presence of Cd in the nutrient solution (+Cd/−Se, +Cd/+SeF and +Cd/+SeR) decreased the total dry biomass by 48%, 45%, and 38%, respectively, as compared to the control treatment (−Cd/−Se). Therefore, the application of Se through the root palliated the negative effect of Cd in the nutrient solution.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…In the first part of the present publication [8], it was shown that the presence of Cd in the nutrient solution (+Cd/−Se, +Cd/+SeF and +Cd/+SeR) decreased the total dry biomass by 48%, 45%, and 38%, respectively, as compared to the control treatment (−Cd/−Se). Therefore, the application of Se through the root palliated the negative effect of Cd in the nutrient solution.…”
Section: Discussionmentioning
confidence: 65%
“…The objective of the present work is to discover how Cd toxicity affects nitrogen and carbon metabolism of pepper plants, and to identify if, among the mechanisms involved in the tolerance of pepper plants to Cd when Se is applied, they are related with the synthesis and accumulation of polyamines and amino acids. This work is part of another publication by Pérez-Millán et al (2021) [8], which demonstrated that the application of Se reduces the concentration and toxicity of Cd in pepper plants.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations